Detrusor after‐contraction on ambulatory urodynamics in symptomatic women. (24th August 2015) - Veeratterapillay, Rajan; Coates, James; Leonard, Ann; Pickard, Robert; Drinnan, Michael; Harding, Chris
<x xml:space="preserve">Abstract</x> Objectives To investigate the association between detrusor after‐contraction and urodynamic parameters in a cohort of patients undergoing urodynamic studies by ambulatory monitoring. Methods All symptomatic adult female patients with non‐neurogenic lower urinary tract dysfunction having ambulatory monitoring over the period January 1998 to January 2014 were included. Urodynamic traces were reviewed to identify detrusor after‐contraction. Measured urodynamic variables were Qmax (mL/s), Vvoid (mL) and Pdet.Qmax (cmH2O). Student's unpaired t‐test was used to compare the mean of the variable in the detrusor after‐contraction and non‐detrusor after‐contraction groups. Results We identified 331 women with a median age of 50 years (range 16–82). Detrusor after‐contraction was seen after at least one void in 122 patients giving a prevalence of 37%. A total of 167 (51%) patients had detrusor overactivity. Diagnosis of detrusor overactivity was associated with the presence of detrusor after‐contraction (P < 0.05). Overall, patients with detrusor after‐contraction had a statistically higher mean Pdet.Qmax (32 vs 28 cmH2O, P = 0.04) and lower mean voided volume (300 vs 378 mL, P < 0.001). Conclusion These findings suggest a relatively high prevalence of detrusor after‐contraction during ambulatory monitoring, and an association between detrusor overactivity, Vvoid, Pdet.Qmax and detrusor after‐contraction recorded during ambulatory monitoring. Therefore, a link between detrusor after‐contractions and the syndrome of overactive bladder can be postulated.